PENGARUH ORGANIZATION LEARNING TERHADAP COMPETITIVE POSITIONING MELALUI INTENSITAS PENGGUNAAN SISTEM INFORMASI AKUNTANSI PADA STUDI KASUS PERUSAHAAN NON MANUFACTURING - Imelda, Beatriz (Business Accounting Review, 2015)
The purpose of this research was to identify the influence of Organization Learning toward Competitive Positioning with Accounting Information System as the mediating variable Non Manufacturing Firms in Surabaya. The variables were: Organization Learning,Â Accounting Information System, and Competitive Positioning. The number of samples were 83 respondents. The data analysis technique used was Partial Least Square. This research showed that Organization Learning had positive influence toward Competitive Positioning; Organization Learning had positive influence toward Accounting Information System, but there was no influence of Accounting Information System on Competitive Positioning. Thatâs why, Accounting Information System was not a mediating variable of Organization Learning towards Competitive Positioning in non manufacturing firms in Surabaya.Â